2021
DOI: 10.1088/1361-6463/abf165
|View full text |Cite
|
Sign up to set email alerts
|

Binary copper oxides as photovoltaic absorbers: recent progress in materials and applications

Abstract: Binary copper oxides are a promising class of p-type semiconductors for solar energy conversion applications due to their particular electrical and optical properties, elemental abundance, and non-toxicity. So far, three phases with different copper ion oxidation states, including cuprous Cu2O, paramelaconite Cu4O3, and cupric CuO, have already been successfully synthesized by thin-film deposition techniques. This work reviews recent progress in determining the physical properties of these three phases from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 130 publications
1
9
0
Order By: Relevance
“…This observation is consistent with the DFT results on the acceptor level of N O at ∼E V + 0.5 eV. 14 Although hydrogen is known to be an abundant impurity in oxides, our understanding of its properties in Cu 2 O is limited. According to Van de Walle and Neugebauer 18 isolated interstitial hydrogen (H i ) is a negative-U center in various semiconductors.…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…This observation is consistent with the DFT results on the acceptor level of N O at ∼E V + 0.5 eV. 14 Although hydrogen is known to be an abundant impurity in oxides, our understanding of its properties in Cu 2 O is limited. According to Van de Walle and Neugebauer 18 isolated interstitial hydrogen (H i ) is a negative-U center in various semiconductors.…”
Section: Introductionsupporting
confidence: 89%
“…14 and references therein). Instead, nitrogen is proposed to mainly replace Cu in its molecular form, as (N 2 ) Cu , 14 which is supported by experimental results showing that nitrogen is present in Cu 2 O predominantly as N 2 . 15 Finally, it is calculated that (N 2 ) Cu has a shallower acceptor level at ∼0.2 eV.…”
Section: Introductionmentioning
confidence: 75%
“…Sample 5 shows a bandgap value around 2.46 eV, close to the value reported for Cu 2 O material. 38,39 In samples 2 and 4, the values obtained (1.74 and 1.86 eV, respectively) cannot be considered as representing the Cu 2 O matrix bandgap since the presence of the nanoparticles induces absorption related to interband transitions in metallic copper. However, the higher the polycrystalline character of the layer (as in the case of sample 2), the higher the density of grain boundaries, which increases the disorder in the crystalline structure.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…These values have been compared with experimental results from other studies to follow the same range as the reported data. ,, In addition to these parameters, dopant concentrations have been included with a donor density of 10 19 cm –3 for ZnO and an acceptor density of 10 14 cm –3 for Cu 2 O thin films. These values were chosen on the basis of average values found in the literature. Additionally, defects were assumed to be neutral, since they are the ones that contribute the most to the Schockley–Read–Hall (SRH) recombination phenomena . In this recombination model, the carrier lifetime is calculated using the following equation: where N t represents the defect density; V th , 10 7 cm/s, the thermal velocity; and σ X the defect capture cross-section with σ n , 10 –14 cm 2 , and σ p , 10 –15 cm 2 , for Cu 2 O and σ n , 10 –15 cm 2 , and σ p , 10 –14 cm 2 , for ZnO …”
Section: Methodsmentioning
confidence: 99%